Efektivitas Fatwa Majelis Ulama Indonesia (MUI) ke-III Tentang Rokok - ayu anggraini; Muhyidin (JOSH: Journal of Sharia, 2024)
One of the results produced by Ijtima’ Ulama of the Indonesian Fatwa Commission III which was held by the MUI (Indonesian Ulema Council) in 2009 in Padang Pajang was a fatwa concerning smoking. In the fatwa issued by the MUI, there are three points in the legal provisions regarding the cigarette law, namely first they agreed that there would be a difference regarding the smoking law, namely between makruh and haram. Secondly, the ijtima participants agreed to give the mandate to the Central MUI to establish a fatwa for the makruh or haram of smoking. Third, the ijtima’ulama agreed that smoking law is illegal for four things, namely smoking in public places, for children, for pregnant women and for the members of the Indonesian Ulama Council. This article seeks to examine the MUI fatwa in terms of its methodology.